Distinctive intrahepatic characteristics of paediatric and adult pathogenesis of chronic hepatitis C infection - Valva, Pamela (2014)
Mechanisms leading to liver damage in chronic hepatitis C (CHC) are being discussed, but both the immune system and the virus are involved. The aim of this study was to evaluate intrahepatic viral infection, apoptosis and portal and periportal/interface infiltrate in paediatric and adult patients to elucidate the pathogenesis of chronic hepatitis C. HCV-infected, activated caspase-3+ and TUNEL+ hepatocytes, as well as total, CD4+, CD8+, Foxp3+ and CD20+ lymphocytes infiltrating portal and periportal/interface tracts were evaluated in 27 paediatric and 32 adult liver samples by immunohistochemistry or immunofluorescence. The number of infected hepatocytes was higher in paediatric than in adult samples (p 0.0078). In children, they correlated with apoptotic hepatocytes (activated caspase-3+r = 0.74, p < 0.0001; TUNEL+r = 0.606, p 0.0017). Also, infected (p = 0.026) and apoptotic hepatocytes (p = 0.03) were associated with the severity of fibrosis. In adults, activated caspase-3+ cell count was increased in severe hepatitis (p = 0.009). Total, CD4+, CD8+ and Foxp3+ lymphocyte count was higher in adult samples (p < 0.05). Paediatric CD8+ cells correlated with infected (r = 0.495, p 0.04) and TUNEL+ hepatocytes (r = 0.474, p = 0.047), while adult ones correlated with activated caspase-3+ hepatocytes (r = 0.387, p 0.04). In adults, CD8+ was associated with hepatitis severity (p < 0.0001) and correlated with inflammatory activity (CD8+ r = 0.639, p 0.0003). HCV, apoptosis and immune response proved to be involved in CHC pathogenesis of both paediatric and adult patients. However, liver injury in paediatric CHC would be largely associated with a viral cytopathic effect mediated by apoptosis, while in adults it would be mainly associated with an exacerbated immune response.